The Biocontrol Functions of Bacillus velezensis Strain Bv-25 Against Meloidogyne incognita - Tian, Xue-liang; Zhao, Xiao-man; Zhao, Song-yu; Zhao, Jian-long; Mao, Zhen-chuan (Frontiers in Microbiology, 2022)
Root-knot nematodes are obligate parasitic nematodes with a wide variety of hosts and cause huge economic losses every year. To screen root-knot nematode biocontrol bacteria, the nematicidal activity of Bacillus velezensis strain Bv-25 obtained from cucumber rhizosphere soil was identified. The results showed that strain Bv-25 has strong nematicidal activity, and the lethality rate of fermentation broth to second instar larvae (J2s) of Meloidogyne incognita was 100% within 12 hours. In addition, Bv-25 can inhibit the egg hatching of M. incognita. Moreover, the active genes ord-1, mpk-1 and flp-18 of J2s were suppressed by Bv-25 fumigation treatment in 48 h. Strain Bv-25 can colonize cucumber roots, the number of bacteria attached to cucumber roots within 24 hours was 5.94×107 CFU/g, effectively reduced the infection rate of M. incognita by 98.6%. The bacteria up-regulated the expression levels of cucumber defense response gene pr1, pr3, and lox1 to induce the cucumber resistance to M. incognita. Potted experiment showed that strain Bv-25 reduced cucumber root knots by 73.8%. The field experiment demonstrated that disease index was reduced by 61.6%, cucumber shoot length increased by 14.4%, and yield increased by 36.5% compared to control. In general, the B. velezensis strain Bv-25 strain have good control effects on root-knot nematodes, and have a potentiality to develop new biocontrol agents.